A tough soft–hard interface in the human knee joint driven by multiscale toughening mechanisms - Wenyue Li; Xiaozhao Wang; Renwei Mao; Dong Li; Hongxu Meng; Ru Zhang; Jinghua Fang; Zhengzhong Kang; Boxuan Wu; Weiwei Ma; Xudong Yao; Chang Xie; et al. (Proceedings of the National Academy of Sciences, 2025)
Joining heterogeneous materials in engineered structures remains a significant challenge due to stress concentration at interfaces, which often leads to unexpected failures. Investigating the complex, multiscale-graded structures found in animal tissue provides valuable insights that can help address this challenge. The human meniscus root–bone interface is an exemplary model, renowned for its exceptional fatigue resistance, toughness, and interfacial adhesion properties throughout its lifespan. Here, we investigated the multiscale graded mineralization structure and their strengthening mechanisms within the 30-micron soft–hard interface at the root–bone junction. This graded interface, featuring interdigitated structures and an exponential increase in modulus, undergoes a phase transition from amorphous calcium phosphate (ACP) to gradually matured hydroxyapatite (HAP) crystals, regulated by location-specific distributed biomolecules. In coordination with collagen fibril deformation and reorientation, the in situ tensile mechanical experiments and molecular dynamic simulations revealed that immature ACP particles debond from the collagenous matrix and translocate to dissipate energy, while the progressively matured HAP crystals with high stiffness pins propagating cracks, thereby enhancing both the toughness and fatigue resistance of the interface. To further validate our findings, we built biomimetic soft–hard interfaces with phase-transforming mineralization which exhibited boosted strength, toughness, and interface adhesion. This interface model is generalizable to other material joints and provides a blueprint for developing robust soft–hard composites across various applications.